Best friends forever [compact disc, abridged] : a novel - Weiner, Jennifer (Simon & Schuster Audio, 2009)
In high school, childhood best friends Addie Downs and Valerie Adler grow apart, with Valerie becoming quite popular and Addie falling out of every social circle. Fifteen years later, though, when a horrific tragedy occurs, Valerie, now the local TV weathergirl, must rely on the lonely Addie for help.